2022
DOI: 10.1186/s13567-022-01056-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of microRNA expression in Salmonella Typhimurium-infected porcine ileum reveals miR-194a-5p as an important regulator of the TLR4-mediated inflammatory response

Abstract: Infection with Salmonella Typhimurium (S. Typhimurium) is a common cause of food-borne zoonosis leading to acute gastroenteritis in humans and pigs, causing economic losses to producers and farmers, and generating a food security risk. In a previous study, we demonstrated that S. Typhimurium infection produces a severe transcriptional activation of inflammatory processes in ileum. However, little is known regarding how microRNAs regulate this response during infection. Here, small RNA sequencing was used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…A study by Huang et al ( 143 ), explored the peripheral blood miRNA expression profile after Salmonella enterica serovar Typhimurium infection revealed that 29 miRNAs had different expressions. In addition, studies with miR-146a induction on the fecal bacterial load in pigs suggest its potential role in modulating the fecal bacterial load in pigs during Salmonella infection ( 144 ). Further, the functional analysis of porcine miR-194a-5p, analogous to human miR-194-5p, revealed its significant role in regulating the expression of the TLR4 gene.…”
Section: Mirnas Involved In Swine Diseasesmentioning
confidence: 99%
“…A study by Huang et al ( 143 ), explored the peripheral blood miRNA expression profile after Salmonella enterica serovar Typhimurium infection revealed that 29 miRNAs had different expressions. In addition, studies with miR-146a induction on the fecal bacterial load in pigs suggest its potential role in modulating the fecal bacterial load in pigs during Salmonella infection ( 144 ). Further, the functional analysis of porcine miR-194a-5p, analogous to human miR-194-5p, revealed its significant role in regulating the expression of the TLR4 gene.…”
Section: Mirnas Involved In Swine Diseasesmentioning
confidence: 99%
“…miRNAs are noncoding RNA molecules of roughly 19 to 25 nt in length, and they can regulate the expression levels of gene by binding to specific messenger RNA (mRNA) sequences [ 17 , 18 ]. In domestic animals, miRNAs have been reported to play a pivotal part in regulating skeletal muscle and fat development as well as immune response [ 19 , 20 , 21 ]. miRNAs are key regulators of FE.…”
Section: Introductionmentioning
confidence: 99%